Fascists and Conservatives : the Radical Right and the Establishment in Twentieth-Century. - Blinkhorn, Martin (Routledge, 1990)
What has between the |radical' and the |conservative' right in twentieth-century Europe? In Fascists and Conservatives thirteen distinguished authorities on the European right explore this major theme within Italy, Germany, Spain, Portugal, France, Britain, Austria, Romania, Greece adn the Nordic countries.